1979
DOI: 10.1126/science.493962
|View full text |Cite
|
Sign up to set email alerts
|

Water, Protein Folding, and the Genetic Code

Abstract: The absolute affinities of amino acid side chains for solvent water closely match their relative distributions between the surface and the interior of native proteins and are associated with a remarkable bias in the genetic code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
143
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 13 publications
2
143
0
1
Order By: Relevance
“…9), various explanations of its organization and the assignment of the 64 triplets have been offered (10,11). It was soon realized that chemically similar amino acids are often encoded by relatively similar codons (12,13) and that very hydrophobic amino acids are encoded by codons having uracil (U) in the second position (14). Our analysis revealed that, in addition to their second position, codons of very hydrophobic amino acids have a remarkably high U content in general (Fig.…”
Section: Analysis Of the Genetic Code In Mrnas Encoding Integral Membmentioning
confidence: 85%
“…9), various explanations of its organization and the assignment of the 64 triplets have been offered (10,11). It was soon realized that chemically similar amino acids are often encoded by relatively similar codons (12,13) and that very hydrophobic amino acids are encoded by codons having uracil (U) in the second position (14). Our analysis revealed that, in addition to their second position, codons of very hydrophobic amino acids have a remarkably high U content in general (Fig.…”
Section: Analysis Of the Genetic Code In Mrnas Encoding Integral Membmentioning
confidence: 85%
“…This difficulty has been noted in the past, and it has been suggested that water-vapor transfer free energies would be a less complicated index of hydropathy (Hine & Mookerjee, 1975). The watervapor partition coefficients for model compounds identical to each of 14 amino acid sidechains were assembled by Wolfenden et al (1979Wolfenden et al ( ,1981 from the Tables published by Hine & Mookerjee (1975). They reported as well experimental determinations for four additional.…”
Section: Experimental Procedures (A) the Computer Programmentioning
confidence: 99%
“…They reported as well experimental determinations for four additional. previously unavailable, values (Wolfenden et al, 1979). All of these values, expressed as transfer free energies between an aqueous solution and the condensed vaport.…”
Section: Experimental Procedures (A) the Computer Programmentioning
confidence: 99%
“…Early work on the crystal structure of hemoglobin and related proteins showed that the side-chains of the more polar amino acid residues tend to be exposed to solvent, whereas less polar side-chains tend to be buried within the interior of globular proteins (1). Later, those tendencies were put to a quantitative test by measuring equilibria of transfer of amino acid side-chains from neutral aqueous solution into less polar environments, such as the vapor phase (2,3) or a nonpolar solvent such as cyclohexane (4), which dissolves only ∼2 × 10 −3 M water at saturation (5) and appears to be devoid of specific interactions with solutes. The water-to-cyclohexane distribution coefficients (K w>c ) of the 20 common sidechains [here termed "hydrophobicities" (6, 7) and expressed in concentration units of mol/L in each phase; SI Appendix] were found to span a range of 15 orders of magnitude at pH 7 and 25°C.…”
mentioning
confidence: 99%
“…Thus, a pyrimidine at the second codon position signals amino acids whose average hydrophobicity is much greater than those coded by a purine at the same position (2,3). The values reported here allow a more detailed analysis, described in a companion paper (16), which reveals that two separate codes for amino acid size and hydrophobicity appear to be embedded in different parts of their tRNA sequences, with size (represented by vapor-to-cyclohexane equilibria) encoded in the acceptor stem, and hydrophobicity (represented by water-to-cyclohexane equilibria) embedded in the anticodon.…”
mentioning
confidence: 99%